Hypothyroidism and Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
A term infant born to a mother with gestational diabetes and a history of hypothyroidism presented with seizures on the 6th day of life that responded to L-thyroxine, in a report from The Children's National Medical Center, Washington, DC.